Smart Device-Machine-To-Machine Approach for Enhancing Communication in MANET Using IoT and Cloud - Kanmani Ruby, Erode Dhanapal; Pushpavalli, M.; Selvarani, Aruliah; Thilagavathy, S. D.; Choubey, Shruti Bhargava; Harika, Dondapati (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Mobile Ad Hoc Networks (MANET) are crucial for the next generation of computing in the Internet of Things (IoT). All devices in a MANET can transfer from one location to another in any direction. Data processing and resource management can be implemented in all components by providing cloud services to users in MANET to access smart devices within the IoT framework. However, security is a major challenge for the growth of Cloud Computing (CC). Establishing a secure network connection takes time and effort. Nevertheless, embracing CC includes frequent outages, improper management, lack of resources, interoperability issues, privacy concerns, and reliability problems. Therefore, to solve this problem, they initially selected the Cluster Head (CH) to calculate the parameters of a mobility and energy node using a weighted metric. Furthermore, the Load Balancing Cluster Head (LBCH) algorithm can reduce the delay in sending and receiving packets through CH. In addition, the variation between the communication workload of each mobile node can be assessed. Then, the Velocity of the IoT node can be calculated using the Cloud Data Transfer Rate (CDTR) approach at the base of the cloud-maintained IoT integration. Finally, the proposed technique can detect the new positions using a Smart Device-Machine-To-Machine (SD-M2M) approach and enhance communication network security. Implementing the proposed method can enhance secure communication in MANET’s IoT structure systematically and efficiently. Simulation results evaluate the algorithm’s performance regarding channel number, throughput, data transmission rate, energy consumption, energy efficiency, network security and packet delivery rate. The proposed method attains a throughput performance of 79% and security performance of 83% in MANET..